Integrating the patient and caregiver voice in the context of pediatric, adolescent, and young adult care: A family-centered approach - Sarah Featherston; Beatriz Rozo; Danielle Buzanga; Alexandra Garcia; Joanne Greene; Laura Salvador; Joan O'Hanlon-Curry (Patient Experience Journal, 2018)
Family-centered care (FCC) is defined as an approach to care coordination founded in collaborative partnerships between healthcare providers, patients and their family caregivers. Amid the enthusiasm for FCC in the pediatric setting, opportunities have been identified to operationalize the engagement of pediatric, adolescent and young adult patients and their caregivers into decision making that translates not only to their healthcare, but also to the context in which care is provided, as well as the research informing their care. At a National Cancer Institute-designated comprehensive cancer center, the Children’s Cancer Hospital was instrumental in designing and implementing patient and family engagement councils to inform institutional policies, guidelines, environment of care and research. The councils include: he Family Advisory Council, the Supportive Care Council, the Young Adult Advisory Council, and the Patient Advisory Council for Teens (imPACT). The development and outcomes of these councils is presented as an exemplar for patient and family engagement that translates to tangible healthcare delivery initiatives.